2007
DOI: 10.1523/jneurosci.0938-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Spatial Perception Dynamically Realigns with Changing Eye Position

Abstract: Audition and vision both form spatial maps of the environment in the brain, and their congruency requires alignment and calibration. Because audition is referenced to the head and vision is referenced to movable eyes, the brain must accurately account for eye position to maintain alignment between the two modalities as well as perceptual space constancy. Changes in eye position are known to variably, but inconsistently, shift sound localization, suggesting subtle shortcomings in the accuracy or use of eye posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 47 publications
(71 reference statements)
14
91
4
Order By: Relevance
“…Even if subjects maintained eccentric eye positions following active head movement, it would not be sufficient to explain our results because the effect of eye position on auditory localization is small (3°for 45°eye turn) compared with differences in auditory localization observed across conditions in the present study (8°difference between Active and Passive conditions for 30°head turn); the small effect of eye position is further reduced in complete darkness (Lewald and Ehrenstein 1996). Although larger effects of eye movements have been reported (Razavi et al 2007), these effects are typically observed only after an eccentric eye position is maintained for an extended period of time. Thus the effect of eye position signals on the current results is likely negligible.…”
Section: Inaccuracy In Auditory Spatial Updating During Active Head Rcontrasting
confidence: 68%
“…Even if subjects maintained eccentric eye positions following active head movement, it would not be sufficient to explain our results because the effect of eye position on auditory localization is small (3°for 45°eye turn) compared with differences in auditory localization observed across conditions in the present study (8°difference between Active and Passive conditions for 30°head turn); the small effect of eye position is further reduced in complete darkness (Lewald and Ehrenstein 1996). Although larger effects of eye movements have been reported (Razavi et al 2007), these effects are typically observed only after an eccentric eye position is maintained for an extended period of time. Thus the effect of eye position signals on the current results is likely negligible.…”
Section: Inaccuracy In Auditory Spatial Updating During Active Head Rcontrasting
confidence: 68%
“…Overall, the Keyboard response method was the most accurate, introducing only an approximate constant frontal bias. This bias is likely related to the fact that the subjects tended to look straight ahead before the stimulus was presented in each Keyboard-run trial, as previous studies reported that sound localization can be biased toward the gaze direction (Razavi et al, 2007). The pattern of results observed in the Open-Eyes-Pointer condition was similar, even though it was less consistent, possibly because the subjects did not use vision to guide their responses to the most lateral targets.…”
Section: Baseline Performancementioning
confidence: 77%
“…This rapid adaptation of auditory space in the direction of eye position in the head applied equally to all experiments reported here and is unlikely to have biased the comparisons across conditions. Eye-position-dependent adaptation has been addressed at length previously by our group (Cui et al 2010a;Dobreva 2010;Razavi et al 2007) and by others (Bohlander 1984;Lewald 1998Lewald , 1997Lewald et al 2000;Ehrenstein 1998, 1996;Lewald and Getzmann 2006;Weerts and Thurlow 1971;Yao and Peck 1997).…”
Section: Wideband Sound Localization In Young Listenersmentioning
confidence: 90%
“…The experimental environment has been described previously (Cui et al 2010a,b;Razavi et al 2007;Zwiers et al 2003). Subjects were seated in a fully enclosed and darkened room (3.0 x 3.7 ϫ 2.7 m) lined with 3-in.…”
Section: Experimental Chamber Target Apparatus and Positioningmentioning
confidence: 99%
See 1 more Smart Citation